2018
DOI: 10.1186/s12877-018-0732-4
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic kidney disease in the elderly: prevalence and clinical correlates

Abstract: BackgroundDiabetic kidney disease (DKD) is a major burden in elderly patients with type 2 diabetes (T2DM). Low estimated glomerular filtration rate (eGFR+, < 60 mL/min/1.73 m2) and albuminuria (Alb+) are essential for the diagnosis of DKD, but their association with clinical variables and quality of care may be influenced by ageing.MethodsHere we investigated the association of clinical variables and quality of care measures with eGFR+ and Alb+ in 157,595 T2DM individuals participating to the Italian Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 60 publications
6
48
1
14
Order By: Relevance
“…Our findings showed that T2DM patients aged 56-65, 66-75, and>75 years had more than 2.8-fold, 5.4-fold, and 27.4-fold higher adjusted ORs for CKD, respectively. This result reaffirms that of previous studies that older age was associated with a higher risk of CKD among T2DM patients 33,37,[39][40][41][42]44 . Cardiovascular disease, obesity, and multimorbidity via endothelial cell dysfunction and sympathetic nervous system activation resulting in increased atherosclerosis, hypertension, and progressive nephrosclerosis are believed to explain the mechanisms underlying older age and the risk of CKD 49,50 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings showed that T2DM patients aged 56-65, 66-75, and>75 years had more than 2.8-fold, 5.4-fold, and 27.4-fold higher adjusted ORs for CKD, respectively. This result reaffirms that of previous studies that older age was associated with a higher risk of CKD among T2DM patients 33,37,[39][40][41][42]44 . Cardiovascular disease, obesity, and multimorbidity via endothelial cell dysfunction and sympathetic nervous system activation resulting in increased atherosclerosis, hypertension, and progressive nephrosclerosis are believed to explain the mechanisms underlying older age and the risk of CKD 49,50 .…”
Section: Discussionsupporting
confidence: 91%
“…According to the Global Burden Disease-CKD study, CKD due to diabetes accounted for 30.7% of CKD populations, in which T2DM was the only cause of CKD to illustration a substantial increase in the age-standardised rate (changed by 9.5% from 1990 to 2017) 32 . Globally, the overall prevalence of CKD among T2DM patients varied at 6.0-39.3% (our result found at 24.4%) 17,25,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] . These discrepancies across different settings may be attributed to the variations in diagnostic methods used and ethnicities such as the black race, which is associated with a greater rate of GFR decline 48 .…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[4] Moreover, these older patients often have concomitant diabetes mellitus contributing to cardiovascular diseases, and etiology of ESKD is multifactorial. [8] Hypertension is cited as the third most common etiology of ESKD locally, after diabetes mellitus and glomerulonephritis. [9] Regardless of adjudication bias in kidney disease causation, the connection between blood pressure control and the risk of worsening nephropathy has been demonstrated in multiple studies.…”
Section: Clinical Epidemiology Of Hypertensive Kidney Diseasementioning
confidence: 99%
“…[203][204][205] Em idosos com diabetes a prevalência de insuficiência renal pode chegar a aproximadamente 50%. 206,207 Com isso, GPCs tem recomendado o uso com cautela destes AINEs em indivíduos com diabetes. 197,198 Entre as CT mais observadas na população estudada, há, ainda, a combinação de doença pulmonar (doença índice), osteoporose (doença que compete) e corticosteroide (medicamento que compete).…”
Section: Análise Dos Dadosunclassified